Efficacy analysis of endoscopic submucosal dissection in gastric adenocarcinoma of fundic gland type: five cases of more than 36 months of follow-up - Li, Yang; Lu, Youzhu; Yu, Chao; Xiao, Jun; Han, Shutang (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: To explore the feasibility, safety, and effectiveness of endoscopic submucosal dissection (ESD) in the treatment of gastric adenocarcinoma of fundic gland type (GA-FG). Methods: A retrospective analysis was performed for lesion characteristics, treatment, and follow-up of 5 cases of GA-FG patients treated with ESD in our endoscopy center from Jan 2010 to Dec 2018. Results: Among the 5 patients, there were 2 males and 3 females (M:F =2:3). The average age was 59.8±14.4 years old. Four lesions were located at the fundus, while 1 case was located 1.5 cm below the dentate line. Five cases were all flat-uplifted (0–IIa). The average operation time was 28.6±9.0 min. All 5 patients underwent complete resection, and all of them achieved complete resection. There was no recurrence of the 5 cases for 36–49 months of follow-up. Conclusions: ESD can be used as a method for the treatment of GA-FG.